Interior Resistance. Issue 1 (March 2021) - Adams, Rod; Milligan, Andy; Simpkins, Nigel
The interior frequently masquerades a resistance to being clean, often demonstrating different levels of hygiene, containment, and control. Yet, it is the–body–inside that simultaneously resists and distributes infection within the mineral contexts of the building. Ever since Van Leeuwenhoek's (1993) discovery of a strange microbial world of bacteria and protozoa, societal, bodily, and spatial interpretations of clean have shifted. Evolving levels of cleanliness continually reposition the interior to become progressively more visually hygienic and meticulously super–clean. While medical need often leads and intensifies infection control, it is personal fastidiousness, compulsion, and media image that shape human attitudes and cultures to grime and dirt. Historically, "homes–of–the–future" reinforce a technologically sanitized prototype, a strain of which persists in the sterility of the ordered "show–home." Each avoids the pathogenic realities of the–body–inside revealing esthetic traces of the Modernist ideals of clean lines and clean living that recur in contemporary images of minimal occupation. As we move to develop new hyper–clean and locked–down pandemic–proof interiors capable of immunizing and shielding occupants, this paper re–evaluates what it means to be clean and how the interior helps to resist and mediate these efforts. As concerns over antimicrobial resistance and interior touching increases, our protection from allergy, disease, and contagion are changing. The interior is increasingly playing a critical role in arbitrating biological infection, either through intelligent cleaning systems, infrastructure, or material science. This paper sets out the existing resistance to, and the conditions for, a new clean interior and posits where and what the future might conceive, including the advancement of immunology by reintroducing "dirt" back into interiors (mirroring Edward Jenner's deliberate infection of humans to develop resistance to smallpox) enabling better biological resistant to the outside world.